Peningkatan Kompetensi Guru Dalam Menerapkan Multi Metode Pembelajaran Melalui Kegiatan In House Training Di SDN Sukamulya Kota Tasikmalaya - Caswita Caswita; Irvan Kristivan (Inovasi-Jurnal Diklat Keagamaan, 2022)
This study aims to describe the role of teachers in improving competence in applying multiple learning methods in the learning process. The research method used is qualitative research. Data collection techniques through interviews, observation and documentation studies. The results showed: (1) The In House Training (IHT) activity took place very well with a score of 94.17. (2) The lesson plans made by In House Training (IHT) participants have achieved the predicate of Very Good with a score of 86.02. (3) The process of learning activities took place very well with a score of 90.87. (4) Student learning outcomes increased with the predicate Good with a value of 84.33. The achievement of students in learning activities received a good predicate with a score of 89.25. (5) The element of well-being (joy) of students in learning activities gets a good predicate with a value of 83.93. This means that students feel happy and have fun participating in learning activities with various learning methods applied by SDN Sukamulya teachers.